Transmisi dan Refleksi Gelombang pada Pemecah Gelombang Ambang Rendah Ganda Tumpukan Batu - Surendro, Bambang; Yuwono, Nur; Darsono, Suseno (Department of Civil Engineering, Diponegoro University, 2014)
Protection of beaches for tourism development, protection planning in addition to aiming to keep the damage to the beach will also need to think about the authenticity and beauty of the beach area . Building protective beaches that can meet these objectives include low threshold breakwaters (submerged breakwater). Some of the excessuse of low threshold breakwaters are: 1. No disturbing beauty of the beach; 2. because construction is under water, then when the wave comes partially absorbed wave energy, will be partially reflected, and the rest will be transmitted; 3. can become breeding grounds for fish, because the construction is hollow. The disadvantages are: 1. requires a large stone with a large number, 2. in the assembly requires a supporting infrastructure such as transport equipment, long bridge, lifting equipment etc, thus requiring a lot of cost. Based on that research conducted by the title of the transmission and reflection of waves on double sumerged breakwater. Methodology of research, conducted with with physical models, and then continued with theoretical studies in order to obtain the equation for calculating the coefficient of wave transmission and wave reflection coefficient. The results showed that to calculate the magnitude of the coefficient of wave transmission and wave reflection coefficient can be approximated by the following equation: , .